Motor competence of children in Singapore using Movement ABC-2 test - Tan, Jernice S.Y.; Chia, Michael (PeerJ, 2024)
Introduction The Movement Assessment Battery for Children, 2nd Edition (MABC-2) test is a valuable tool for identifying motor delays in children globally. However, there has been a lack of data for children in Singapore. Methods This study compared 175 children in Singapore (SG) aged 3–6 years to MABC-2 data based on the United Kingdom (UK) population, using statistical tests to analyze age, country, and gender effects on motor competence. Results The results showed a positive age effect across all tasks, with SG children excelling in balance but lagging in aiming and catching tasks compared to UK children. The interaction between age and country yielded mixed results, favoring different groups at various ages. Additionally, girls displayed better manual dexterity and static balance than boys. Conclusion Encouraging more physical activities, especially those involving object manipulation, is crucial for SG children. Establishing local norms for the MABC-2 in Singapore and considering country-specific factors in motor competence evaluations can enhance early intervention strategies. These findings emphasize the importance of tailored approaches to address motor skill development in SG children.
Keywords: Motor assessment; Manual dexterity; Aiming; Throwing; Catching; Balance